(untitled) (Homiletic, 2024)
In this article, I present nineteenth-century preacher Zilpha Elaw as a model for a twenty-first-century homiletic. I discuss particularity, as understood through deep interiority and contemplation, as the key to connecting with other beings. As preachers, we have the ability and the responsibility to model the need for and benefits of understanding and owning our particularities and to guide others in embracing their particularities in ways that affirm self and community. Thanks to the incomparable gifts of African American contemplative preachers, I believe that we can bridge innate differences and societally created divisions through a psycho-spiritual interiority that acknowledges and encourages communication in the spiritual realm. In conjunction with Zilpha Elaw’s life and work, I also engage the contemplative work of preacher, mystic, and theologian Howard Thurman and the scholarship of Womanist theologians Phillis Sheppard and Karen Baker-Fletcher. The writings and lived experiences of these four African Americans, Elaw, Thurman, Sheppard, and Baker-Fletcher, set forth the importance of spirituality, interiority, and particularity that opens the doors for understanding and communication across societally created racial divides.